일과성 전기억상실증으로 진단된 환자 치험 2례 - 오경민; Kyong Min Oh; 양동호; Dong Ho Yang; 조윤송; Youn Song Cho; 김보경; Bo Kyong Kim (동의신경정신과학회지, 2008)
Transient global amnesia(TGA) is a clinical syndrome characterized by sudden, temporary dysfunction of anterograde and recent retrograde memory without other neurologic deficits. Different hypotheses have been considered for its etiology, but it still remains obscure. Recently the diffusion-weighted magnetic resonance imaging(DWI), has been considered as the sensitive tool to detect small punctate hyperintense lesions in the hippocampus in transient global amnesia(TGA). We report two TGA cases, all of them answers to TGA clinical criteria, and one of them showed two dot like high signal intense foci in Rt. hippocampus on DWI.